Social network data analysis (III) - Sze, Kit Ying. (2012)
Among the younger generation, social networks have now become a big part of their life. Most social networks now do interact with one another; however this interaction is not enough. Ifttt.com has come up with a brilliant idea to link the functions of different social networks together.